2009
DOI: 10.1108/09556220910959954
|View full text |Cite
|
Sign up to set email alerts
|

C2CAD: a sustainable apparel design and production model

Abstract: Purpose -The purpose of this paper is to develop and implement a new sustainable apparel design and production model, cradle to cradle apparel design (C2CAD), that provides guidelines for apparel designers and manufacturers to solve some of the sustainability problems related to apparel production. Design/methodology/approach -The C2CAD model was developed by integrating McDonough and Braungart's "cradle to cradle" model into existing apparel design and production models. Knitwear design and production was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 10 publications
5
30
0
1
Order By: Relevance
“…The author identifies that the TA industry has the highest priority to implementing cleaner production. Jin Gam et al (2009) propose a “cradle to cradle apparel design” strategy for the sustainable production to help the practitioners to deal with the sustainability problems in fashion production. The authors uncover that production with the proposed model can achieve good function and colour fastness.…”
Section: Identify Sustainable Practices In the Fscm Literaturementioning
confidence: 99%
“…The author identifies that the TA industry has the highest priority to implementing cleaner production. Jin Gam et al (2009) propose a “cradle to cradle apparel design” strategy for the sustainable production to help the practitioners to deal with the sustainability problems in fashion production. The authors uncover that production with the proposed model can achieve good function and colour fastness.…”
Section: Identify Sustainable Practices In the Fscm Literaturementioning
confidence: 99%
“…Connor-Crabb [34] examined three tools for sustainable fashion design through interviews with the tool developers to determine barriers and opportunities for tool use. The majority of the literature discusses the development of a particular tool, predominately through the description of case studies [19,20,[29][30][31][34][35][36]. Other studies have identified barriers for designers adopting these tools for sustainable design.…”
Section: Ted's Ten [32]mentioning
confidence: 99%
“…Firstly, it provides an overview of Slow Fashion in terms of price point, and the chosen pricing strategies [15]. Ethical Slow Fashion consumers demand goods that are produced in "sweat-free" manufacturing, and various studies have shown that, in such instances, people are willing to accept a higher price tag (e.g., [6,16,17]). One in three respondents were defined as highly involved in the Slow Fashion group, and thus willing to accept a 30 to 40 percent price premium compared to Fast Fashion products [14].…”
Section: Pricementioning
confidence: 99%